Thirty Years of Managerial Mental Representations: A Review Guiding Conceptualization and Future Research - Becker, Philipp Benedikt; Laureiro-Martinez, Daniella; Zagorac- Uremović, Zorica (Journal of Management, 2026)
Managerial mental representations (MMRs) are mental constructs that structure cognitive content to guide perception and interpretation. MMRs have been examined across a broad spectrum of management research contexts, leading to the use of numerous related terms such as “mental representation,” “schema,” “mental model,” “cognitive frame,” “cognitive map,” and “mindset.” This proliferation of terms has caused considerable definitional overlap and ambiguity. To foster definitional clarity, this review systematically analyzes 206 articles employing any of 33 MMR terms used during the past 30 years. We identify the conceptual and functional definition facets of MMRs and use them to analyze commonalities and differences among the most prominent MMR terms. We further examine both established and emerging discussions surrounding the characteristics of MMRs. Established discussions focus on MMR content and levels of analysis, while emerging discussions explore MMR permanence and implicitness. We propose suggestions to advance each conversation. Based on this comprehensive analysis, we create a guiding framework aiding future research to conceptualize MMRs and navigate terminology choices. Finally, we propose two future research directions: integrating the content and process perspectives on MMRs and applying an MMR lens to examine the emergence of artificial intelligence in organizations.